Development and management of gastrointestinal symptoms in long-term COVID-19 - He, Kai-Yue; Lei, Xin-Yuan; Zhang, Lei; Wu, Dan-Hui; Li, Jun-Qi; Lu, Li-Yuan; Laila, Umm E.; Cui, Cui-Yun; Xu, Zhi-Xiang; Jian, Yong-Ping (Frontiers in Microbiology, 2023)
Background: Emerging evidence reveals that SARS-CoV-2 possesses the capability to disrupt the gastrointestinal (GI) homeostasis, resulting in the long-term symptoms such as loss of appetite, diarrhea, gastroesophageal reflux, and nausea. In the current review, we summarized recent reports regarding the long-term effects of COVID-19 (long COVID) on the gastrointestine. Objective: To provide a narrative review of abundant clinical evidence regarding the development and management of long-term GI symptoms in COVID-19 patients. Results: Long-term persistent digestive symptoms are exhibited in a majority of long-COVID patients. SARS-CoV-2 infection of intestinal epithelial cells, cytokine storm, gut dysbiosis, therapeutic drugs, psychological factors and exacerbation of primary underlying diseases lead to long-term GI symptoms in COVID-19 patients. Interventions like probiotics, prebiotics, fecal microbiota transplantation, and antibiotics are proved to be beneficial in preserving intestinal microecological homeostasis and alleviating GI symptoms. Conclusion: Timely diagnosis and treatment of GI symptoms in long-COVID patients hold great significance as they may contribute to the mitigation of severe conditions and ultimately lead to the improvement of outcomes of the patients.